Shift of close-packed basal planes as an order parameter of transitions between antiferromangetic phases in solid oxygen: II. Temperature/pressure dependence of sound velocities and lattice parameters: Classical Cryocrystals - Gomonay, E.V.; Loktev, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
In the present paper we generalize a phenomenological model developed by Gomonay and Loktev (Fiz. Nizk. Temp. 31, 1002 (2005)) for the description of magnetostructural phase transitions and related peculiarities of elastic properties in solid oxygen under high pressure and/or temperature below 40 K. We show that variation of all the lattice parameters in the vicinity of a–b phase transition is due to both the shift of basal closed-packed planes and appearance of the long-range magnetic order. Competition between these two factors from one side and lattice compression below Tab from another produces nonmonotonic temperature dependence of lattice parameter b (along monoclinic axis). Steep decrease of the sound velocities in the vicinity of Tab can be explained by the softening of the lattice with respect to shift of the close-packed planes (described by the constant K2) prior to phase transition point. We anticipate an analogous softening of sound velocities in the vicinity of a–d phase transition and nonmonotonic pressure dependence of sound velocities in a phase.